A supramolecular Tröger's base derived coordination zinc polymer for fluorescent sensing of phenolic-nitroaromatic explosives in water. Issue 2 (8th November 2016) - Shanmugaraju, Sankarasekaran; Dabadie, Charlyne; Byrne, Kevin; Savyasachi, Aramballi J.; Umadevi, Deivasigamani; Schmitt, Wolfgang; Kitchen, Jonathan A.; Gunnlaugsson, Thorfinnur
Abstract : A Tröger's base functionalized luminescent nanoscale Zn(II) coordination polymer (TB-Zn-CP ) is synthesized and used as selective fluorescence sensor for phenolic nitroaromatics in water. Abstract : A V-Shaped 4-amino-1, 8-napthalimide derived tetracarboxylic acid linker (L ; bis-[ N -(1, 3-benzenedicarboxylic acid)]-9, 18-methano-1, 8-naphthalimide-[ b, f ][1, 5]diazocine) comprising the Tröger's base (TB) structural motif was rationally designed and synthesised to access a nitrogen-rich fluorescent supramolecular coordination polymer. By adopting the straight forward precipitation method, a new luminescent nanoscale Zn(ii ) coordination polymer (TB-Zn-CP ) was synthesized in quantitative yield using Zn(OAc)2 ·2H2 O and tetraacid linkerL (1 : 0.5) in DMF at room temperature. The phase-purity of as-synthesisedTB-Zn-CP was confirmed by X-ray powder diffraction analysis, infra-red spectroscopy, and elemental analysis. Thermogravimetric analysis suggests thatTB-Zn-CP is thermally stable up to 330 °C and the morphological features ofTB-Zn-CP was analysed by SEM and AFM techniques. The N2 adsorption isotherm of thermally activatedTB-Zn-CP at 77 K revealed a type-II reversible adsorption isotherm and the calculated Brunauer–Emmett–Teller (BET) surface area was found to be 72 m 2 g −1 . Furthermore, TB-Zn-CP displayed an excellent CO2 uptake capacity of 76 mg g −1 at 273 K and good adsorption selectivity for CO2 over N2 and H2 . The aqueous suspension of as-synthesizedTB-Zn-CP showed strong green fluorescence ( λ max = 520 nm) characteristics due to the internal-charge transfer (ICT) transition and was used as a fluorescent sensor for the discriminative sensing of nitroaromatic explosives. The aqueous suspension ofTB-Zn-CP showed the largest quenching responses with high selectivity for phenolic-nitroaromatics (4-NP, 2, 4-DNP and PA) even in the concurrent presence of other potentially competing nitroaromatic analytes. The fluorescence titration studies also provide evidence thatTB-Zn-CP detects picric acid as low as the parts per billion (26.3 ppb) range. Furthermore, the observed fluorescence quenching responses ofTB-Zn-CP towards picric acid were highly reversible. The highly selective fluorescence quenching responses including the reversible detection efficiency make the nanoscale coordination polymerTB-Zn-CP a potential material for the discriminative fluorescent sensing of nitroaromatic explosives.